(untitled) (International Journal of Environmental Sciences, 2025)
Jaundice is a disease, which is characterized by yellow staining ofthe skin and sclera by abnormally high blood levels of the bile pigment bilirubin. The yellowing extend stoother tissuesand body fluids. Bilirubin, a tetrapyrrole pigment, is a broken-down product of heme (ferroprotoporphyrin IX). About 70 to 80% of the 250 to 300 mg ofbilirubin produced each day is derived from the breakdown of hemoglobinin senescent red blood cells. The remainder comes from prematurely destroyed erythroid cells in bone marrow and from the turnover of hemoproteins such as myoglobin and cryptochromes found in tissues throughoutthebody.The philosophy of Unani system of medicine is based on thehumoral theory. The theory was central theme to the teachings of Hippocrates and Galenandi tbe came the dominant theoryin Europe form any centuries. Asperthe Unani system of medicine, the causeof jaundice is the accumulation of yellow or black humours in thecutaneous tissue and its nearby tissues. Based upon the nature of discoloration jaundice is classified into two types: Yellow Jaundice and Black Jaundice.In the allopathic system there lack of effective drugs for jaundice. Some hepatoprotective drugs are available but many side effects are associated with the mduet otheir chemical composition. InUnanisystem of medicine, this disease can be cured with completely natural and non- invasivemethods.